Genetic variation in the symbiont partners in the endangered macrolichen Seirophora villosa (Teloschistaceae: Ascomycota) - Garrido-Benavent, Isaac; Molins, Arántzazu; Barreno, Eva (Botanical journal of the Linnean Society, 2022)
Abstract The decline observed in many populations of highly sensitive lichens has led to the inclusion of some species on regional Red Lists, but this has seldom been accompanied by an examination of the genetic variation of the fungal and algal symbiotic partners. Here, the red-listed epiphytic lichen Seirophora villosa was surveyed in 14 Mediterranean coastal populations to examine the genetic diversity of both partners. The geographical distribution of four-locus haplotypes followed the same trend in mycobiont and photobiont data sets, some being widespread and others restricted to single localities. The fungus showed a moderate selectivity in its photobiont choice, associating with two undescribed Trebouxia microalgae with a biased distribution across the western Mediterranean. One alga species occurred exclusively in the Italian Peninsula. This region also hosted the highest number of haplotypes for both symbionts. The use of 454-pyrosequencing revealed no clear signs of algal coexistence within selected thalli. The phylogenetic reconstruction for the mycobiont showed uncertain limits among Seirophora spp., stressing the need for further taxonomic evaluation. Additionally, we found that Ramalina lacera, a co-occurring epiphytic lichen in the studied area, shared photobiont genotypes with S. villosa. Our results thus suggest that the protection not only of the red-listed species S. villosa, but also of the whole epiphytic lichen community investigated here might be advisable.